Aeromonas and Human Health Disorders: Clinical Approaches - Pessoa, Rafael Bastos Gonçalves; Oliveira, Weslley Felix de; Correia, Maria Tereza dos Santos; Fontes, Adriana; Coelho, Luana Cassandra Breitenbach Barroso (Frontiers in Microbiology, 2022)
The genus Aeromonas comprises more than thirty Gram-negative bacterial species and naturally inhabitants from aquatic environments. These microoganisms, commonly regarded as pathogens of fish and several other animals, have been gaining prominence on medical trial due to its ability to colonize and infect human beings. Besides water, Aeromonas are widely spreaded on most varied sources like soil, vegetables and food; Although its opportunistic nature, they are able to cause infections on immunocompromised or immunocompetent patients. Aeromonas species regarded as potential human pathogens are usually A. hydrophila, A. caviae and A. veronii biovar sobria. The main clinical manifestations are gastrointestinal tract disorders, wound and soft tissue infections, as well as septicemia. Regarding to antibiotic responses, the bacteria present a diversified susceptibility profile and shows inherence resistance to ampicillin. Aeromonas, as an ascending genus in microbiology, has been carefully studied aiming comprehension and development of methods for detection and medical intervention of infectious processes, not fully elucidated in medicine. This review focuses on current clinical knowledge related to human health disorders caused by Aeromonas to contribute on development of efficient approaches able to recognize and impair the pathological processes.